Influence and evaluation of saturated soil shield construction on existing highway. Issue 1 (14th October 2020) - Xu, Liuqi; Wu, Chongfu; Wang, Liwei; Xu, Shuangjun
Abstract: In order to study the shield construction under an existing highway, the initial displacement and the excess pore water pressure solution from Biot consolidation equation were used to derive the analytical solutions of the vertical deformation and pore water pressure of saturated soil caused by the frontal friction and side friction of the cutterhead. In addition, by introducing the layered method and combining it with other theoretical analytical equations, the expressions of total vertical deformation and total pore water pressure caused by tunnel excavation with different overlying materials were obtained. The simulation results on an engineering project showed that the angle α between the direction of the road and the propulsion axis of the shield had a significant influence on the surface settlement of the road. When the angle α was increased, the settlement curve had higher variation; but the variation would not exceed the maximum settlement value above the shield axis. When the road was perpendicular to the shield axis, a critical point of the road bulging and settlement was formed above the incision. Due to the grinding resistance of the cutterhead, the pore water pressure under the roadbed was distributed asymmetrically on both sides of the shield axis.